2020
DOI: 10.1371/journal.pntd.0008195
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal protozoan infections among children 0-168 months with diarrhea in Mozambique: June 2014 - January 2018

Abstract: Background Intestinal parasites such as Cryptosporidium spp., Giardia lamblia and Entamoeba histolytica can cause severe diarrhea, especially among children in developing countries. This study aims to determine the frequency of Cryptosporidium spp., Giardia lamblia and Entamoeba histolytica in children with diarrhea and identify risk factors for infection. Methodology We conducted a cross-sectional study in children aged 0-168 months hospitalized with diarrhea in three regions of Mozambique, from June 2014 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
0
29
1
2
Order By: Relevance
“…The result in this study showed less frequency as compared to the finding reported in Mozambique (12%) among diarrheic hospitalized children. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The result in this study showed less frequency as compared to the finding reported in Mozambique (12%) among diarrheic hospitalized children. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Hospital Central da Beira (HCB) in Sofala; Hospital Geral de Quelimane (HGQ) in Zambézia, and Hospital Central de Nampula (HCN) in Nampula. ViNaDia’s methodology has been previously described [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…is the most attributable to moderate-to-severe diarrhoea in children younger than five in sub-Saharan Africa and Asia [ 3 ]. The second and third most common intestinal protozoa identified in children with diarrhoea are Giardia lamblia and Entamoeba histolytica , respectively [ 5 7 ] .…”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis of a surveillance system in four provinces of Mozambique indicated Nampula province as the one with the highest risk of infection for Cryptosporidium spp. in children younger than 15 years [ 5 ]. Nampula province has poor health indicators, with recurrent reports of cholera outbreaks [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation